PENERAPAN ALGORITMA C4.5 TERHADAP DIAGNOSA PENYAKIT DEMAM TIFOID BERBASIS MOBILE - Ihsan Ihsan; Rusda Wajhillah (Swabumi, 2015)
The use of gadgets in today is not something new anymore. Gadgets can allow a person to perform activities ofinformation. This is used to create mobile-based applications in the use of artificial intelligence in the world ofhealth. Here is a tool used eclips and database use sqlite3 with android OS usage targets. Typhoid is an acutesystemic disease caused by salmonella typhimurium. In the world, the incidence of typhoid fever is estimated toreach 16 million cases annually. More than 600,000 people die every year due to this disease. Based on the dataprocessing of typhoid fever Waluran Health Centers using the algorithm C4.5 obtained 15 rule/decision treeswere applied in the development of mobile-based applications as the basis for the decision. Utilization datamining in this application is a manifestation of artificial intelligence in mobile-based information system inparticular. The same practice will help facilitate the gadget users to diagnose the disease at an early stage oftyphoid fever using existing symptoms.